Education for patients and clients - Coates, Vivien E. (Vivien Elizabeth), 1957- (Routledge essentials for nurses., 1999)
Education for Patients and Clients sets out basic principles for providing patient education as an integral part of nursing care. It challenges the view that simply giving information is enough and investigates strategies for making education as effective as possible. The author explores:*the effect of psychosocial factors such as personal beliefs and family support on our behaviour *the importance of taking such factors into account when planning education for patients and clients*compliance and non-compliance*the role of the nurse as educator*the patient's rig.